2021
DOI: 10.11646/phytotaxa.500.3.5
|View full text |Cite
|
Sign up to set email alerts
|

<strong><em>Impatiens bullatisepala</em> (Balsaminaceae), a new species from Guizhou, China</strong>

Abstract: Impatiens bullatisepala (Balsaminaceae), a new species supported by morphological and phylogenetic evidence from Fanjing Mountain, Guizhou province in China, is described here. It is morphologically similar to I. davidii but can be distinguished by its dorsally ridged lateral sepals with sunk reticulate veins and bullate projections on abaxial surface, 2–2.5 cm deep saccate lower sepal with ca. 0.8 cm long narrowly triangular tip at the mouth, and broadly ovate dorsal petal. Phylogenetic analyses of a combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 1,274 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Specimens were collected, preserved, and deposited in the Herbarium of Wuhan Botanical Garden, Chinese Academy of Sciences (HIB) for further identification. We then dissected the flower and carefully reviewed related literature [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]36,37] and herbaria specimens in a bid to ascertain the identity of the collected species. However, we were unable to match the new plants with any described species based on morphology.…”
Section: Identification and Description Of New Taxonmentioning
confidence: 99%
See 1 more Smart Citation
“…Specimens were collected, preserved, and deposited in the Herbarium of Wuhan Botanical Garden, Chinese Academy of Sciences (HIB) for further identification. We then dissected the flower and carefully reviewed related literature [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]36,37] and herbaria specimens in a bid to ascertain the identity of the collected species. However, we were unable to match the new plants with any described species based on morphology.…”
Section: Identification and Description Of New Taxonmentioning
confidence: 99%
“…The Flora of China lists 227 species, of which 187 are endemic [14]. According to Du et al [15], a total of 69 new taxa of Impatiens have been described in China between 2000 and 2019, and 13 new taxa [16][17][18][19][20][21][22][23][24][25][26][27][28] and three new records [28][29][30] have been published in the last two years, bringing the total species reported for China to nearly 290.…”
Section: Introductionmentioning
confidence: 99%
“…The results of our phylogenetic reconstruction show that the longifilamenta group in Impatiens is a phylogenetically and morphologically cohesive group (Figure 7). As is currently known, this group consists of 25 species growing as annual herbs, characterized by 1-3 flowered racemose inflorescence, and basal lobes of lateral united petals having an apex with a filamentous appendage [5,13,14,[19][20][21][22]. The morphological characteristics of lateral sepals, lower sepals, and lateral united petals have a taxonomic significance within these species, crucial for their identification.…”
Section: Taxonomic Insightsmentioning
confidence: 99%
“…Due to their beautiful appearance and long flowering period, many species of Impatiens are grown all over the world as ornamental plants [7]. Many new species of Impatiens have been discovered and described in recent years [8][9][10][11][12][13][14][15]. There are more than 280 species of Impatiens distributed in China [5,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a few new species have also been found in the northern temperate regions of Europe, Russia and China, as well as North America (Liao et al 2021). Currently, there are more than 349 species of Impatiens in China (Yuan et al, in press) which are distributed mainly in the southwest and northwest mountainous regions, especially in southwest Provinces (including Guizhou, Yunnan, Sichuan) (Chen 2001;Chen et al 2007;Cai et al 2015;Kuang 2015;Tan et al 2015;Ding et al 2016Ding et al , 2017Xia et al 2019;Gu et al 2021;Liao et al 2021;Peng et al 2021b;Song et al 2021a, b, c) and 61 species of Impatiens have been reported in Guizhou Province (Xiong and Yang 2009;Cong 2010;Kuang et al 2014;Luo and Deng 2015;Peng et al 2021a;Yu et al 2021;Yuan et al in press).…”
Section: Introductionmentioning
confidence: 99%